A Model-Driven Approach for Code Generation for Web-based Information Systems Built with Frameworks - Almeida, Nilber Vittorazzi de; Campos, Silas Louzada; Souza, Vítor E. Silva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
In the field of Web Engineering, there are several methods proposed for the development of Web-based information systems (WISs). FrameWeb is a method that aims to develop WISs that use certain types of frameworks in their architecture, proposing models that incorporate concepts of these frameworks during system design. The method’s modeling language is based on Model-Driven Development techniques, making it extensible to support different frameworks and development platforms. In this paper, we present a code generation tool for FrameWeb which harnesses the method’s extensibility by being based on its language’s meta-models. The tool works with an associated visual editor for FrameWeb models and showed promising results in initial evaluation efforts.